2019
DOI: 10.2147/amep.s191470
|View full text |Cite
|
Sign up to set email alerts
|

<p>Coaching by design: exploring a new approach to faculty development in a competency-based medical education curriculum</p>

Abstract: As curricula move from a time-based system to a competency-based medical education system, faculty development will be required. Faculty will be asked to engage in the observation, assessment and feedback of tasks in the form of educational coaching. Faculty development in coaching is necessary, as the processes and tools for coaching learners toward competence are evolving with a novel assessment system. Here, we provide a scoping review of coaching in medical education. Techniques and content that could be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 87 publications
0
59
0
Order By: Relevance
“…As expected, there were differences and similarities in use of the R2C2 in-the-moment model compared to its use in formal meetings with physicians and residents in discussions that drew on collated data. 3,4,11,12 Of necessity, in-the-moment discussions were shorter, yet participants indicated that all 4 phases of the model remained important. They pointed out the need to use communication approaches and phrases within each phase that would engage the learner and yield an impactful conversation in the brief period of time available in busy clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As expected, there were differences and similarities in use of the R2C2 in-the-moment model compared to its use in formal meetings with physicians and residents in discussions that drew on collated data. 3,4,11,12 Of necessity, in-the-moment discussions were shorter, yet participants indicated that all 4 phases of the model remained important. They pointed out the need to use communication approaches and phrases within each phase that would engage the learner and yield an impactful conversation in the brief period of time available in busy clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Coaching in the moment requires specific communication and facilitative strategies to engage the learner and ensure commitment, similar to more longitudinal coaching. 12,22,23 Specific differences arose in wording for phase 1, where relationship building differed between residents who worked with the supervisor for a brief time and those with a longitudinal relationship. As reported in earlier research related to feedback, 4,12,24,25 participants confirmed that relationship building was critical to success of the learning conversation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations